The effect of feeding fermented distillers' grains diet on the intestinal metabolic profile of Guanling crossbred cattle - Luo, Xiaofen; Zhang, Tiantian; Xu, Duhan; Zhu, Mingming; Zhang, Junjie; Zhang, Rong; Hu, Qian; Wang, Yongxuan; He, Guangxia; Chen, Ze; Mei, Shihui; Zhou, Bijun; et al. (Frontiers in Veterinary Science, 2023)
Fermented distiller's grains (FDG)-based diets are nutritious and can improve the growth and intestinal immunity in livestock. However, there is limited research examining the effect of feeding FDG-based diets on changes in intestinal metabolites and related pathways in livestock. In this study, nine Guanling crossbred cattle (Guizhou Guanling Yellow cattle × Simmental cattle) were selected and randomly divided into a basal diet (BD) group and two experimental groups fed with FDG replacing 15% and 30% of the daily ration concentrates (FDG-Case A and FDG-Case B), respectively, with three cattle in each group. Fresh jejunum (J) and cecum (C) tissues were collected for metabolomic analysis. Differential metabolites and metabolic pathways were explored by means of univariate and multivariate statistical analysis. Compared with the J-BD group, 30 and 100 differential metabolites (VIP > 1, p < 0.05) were obtained in the J-FDG-Case A group and J-FDG-Case B group, respectively, and the J-FDG-Case B vs. J-FDG-Case A comparison revealed 63 significantly differential metabolites, which were mainly divided into superclasses including lipids and lipid-like molecules, organoheterocyclic compounds, and organic acids and derivatives. Compared with the C-BD, 3 and 26 differential metabolites (VIP > 1, p < 0.05) were found in the C-FDG-Case A group and C-FDG-Case B group, respectively, and the C-FDG-Case B vs. C-FDG-Case A comparison revealed 21 significantly different metabolites, which were also mainly divided into superclasses including lipids and lipid-like molecules, organoheterocyclic compounds, and organic acids and derivatives. A total of 40 metabolic pathways were identified, with a significance threshold set at p < 0.05. Among them, 2, 14, and 18 metabolic pathways were significantly enriched in the J-FDG-Case A vs. J-BD, J-FDG-Case B vs. J-BD, and J-FDG-Case B vs. J-FDG-Case A comparisons, respectively. Meanwhile, 1, 2, and 3 metabolic pathways were obtained in the C-FDG-Case A vs. C-BD, C-FDG-Case B vs. C-BD, and C-FDG-Case B vs. C-FDG-Case A comparisons, respectively. Furthermore, four significant metabolic pathways, namely insulin resistance, biosynthesis of unsaturated fatty acids, linoleic acid metabolism, and primary bile acid biosynthesis, were significantly enriched in Guanling crossbred cattle fed FDG diets. These results suggest that feeding FDG diets may promote the growth and intestinal immunity of Guanling crossbred cattle by regulating metabolic patterns of lipid compounds and related metabolic pathways. This study sheds light on the potential metabolic regulatory mechanisms of FDG diets and offers some references for their use in livestock feed.